Study on Red Cell Indices in Chronic Liver Disease in Tertiary Level Hospital (Journal of Medicine, 2024)
Background: Chronic liver disease (CLD) in the clinical context is a disease process of the liver that involves a process of progressive destruction and regeneration of the liver parenchyma leading to fibrosis and cirrhosis. Liver diseases are frequently associated with hematological abnormalities. Bleeding and defective blood coagulation contributes to the anemia in CLD patients. Other mechanisms of anemia include aplastic anemia secondary to previous hepatitis, or side effects of treatment of hepatitis with chemotherapeutic agent. Other different factors, such as malabsorption, malnutrition or direct toxic effect also contribute to hematological abnormalities. The examination of complete blood count is common, economically cheap and readily available laboratory procedure. Red cell indices are valuable in the evaluation of morphologic characteristic of anaemias or hematological abnormalities in CLD patients.Objectives: To assess the red cell indices in chronic liver disease patients.Materials & method: This descriptive type of cross-sectional study was conducted in Department of Medicine, Dhaka Medical College Hospital, Dhaka, among 75 cases of Chronic liver disease patients. Samples were selected by purposive sampling technique. Detail demographic data were collected from the patients and recorded in structured case report form. Clinical examination and relevant investigation were done meticulously. Data was processed and analysed with the help of computer program SPSS and Microsoft excel. Quantitative data expressed as mean and standard deviation and qualitative data as frequency and percentage. Results was presented by tabulation and graphical presentation in the form of tables, pie chart, graphs, bar diagrams, histogram & charts etc.Result: Maximum number of patients, 37(49.3%) were between 31-40 years of age with mean age of the patient was 37.58 ± 8.23 years. Out of 75 cases 58(77.0%) patients were male and 17(23.0%) were female. Male-female ratio was 3.34:1. Majority of patients belonged to Child Pugh score B. Prevalence of anaemia was 54(72%) in CLD patients. Microcytic anaemia was predominant and Normocytic anaemia was second most common. Hb concentration & MCV decreases with the severity of Child Pugh score. Abnormalities of red cell indices were positively associated with severity of CLD.Conclusion: Present study concluded that chronic liver diseases are associated with hematological abnormalities. Patients with severe hepatocellular disease develop defects  of  blood  coagulation  as  a  consequence of endothelial  dysfunction,  thrombocytopenia,  deficiencies of coagulation factors and various associated disorders. In overall patients, Child Pugh class C cases had significant low hemoglobin in comparison to rest of group. Assessing the severity and type of anaemia by red cell indices is a useful tool for proper treatment, prognosis in patients of CLD for reducing the mortality and morbidity.J MEDICINE 2024; 25: 41-45